Advances in antibiotic therapy in the critically ill. Issue 1 (December 2016) - Vincent, Jean-Louis; Bassetti, Matteo; François, Bruno; Karam, George; Chastre, Jean; Torres, Antoni; Roberts, Jason; Taccone, Fabio; Rello, Jordi; Calandra, Thierry; De Backer, Daniel; Welte, Tobias; et al.
Abstract Infections occur frequently in critically ill patients and their management can be challenging for various reasons, including delayed diagnosis, difficulties identifying causative microorganisms, and the high prevalence of antibiotic-resistant strains. In this review, we briefly discuss the importance of early infection diagnosis, before considering in more detail some of the key issues related to antibiotic management in these patients, including controversies surrounding use of combination or monotherapy, duration of therapy, and de-escalation. Antibiotic pharmacodynamics and pharmacokinetics, notably volumes of distribution and clearance, can be altered by critical illness and can influence dosing regimens. Dosing decisions in different subgroups of patients, e.g., the obese, are also covered. We also briefly consider ventilator-associated pneumonia and the role of inhaled antibiotics. Finally, we mention antibiotics that are currently being developed and show promise for the future.